COMPATIBILITY OF DIFFERENT OILS WITH BEAUVERIA BASSIANA, A POTENTIAL ENTOMOPATHOGENIC FUNGUS - S. SANGAMITHRA; S. JEYARANI; K. RAMARAJU (The Bioscan, 2015)
Beauveria bassiana, commonly known as white muscardine fungus is considered to be an potential entomopathogen.Formulation and application techniques play a significant role in success of entomopathogens in field circumstances. Oil formulation of entomopathogens may be promoted for their enhanced infectivity, prolonged persistence and increased shelf life. The compatibility of six oils viz., Neem, Pungam, Castor, Mahua, Corn and Paraffin were investigated under in vitro condition by following poison food technique, to explore suitable oil based carrier for Beauveria bassiana (Bb 112). The vegetative growth and sporulation were recorded on10th and 15th day after inoculation and compatibility of oils were worked out. Among the oils tested, Neem, Castor, Mahua, Corn, Paraffin at1, 2, 3, 5 and 10 percentage were compatible with Beauveria bassiana. Pungam oil was found to be not compatible (T factor - 7.90). Paraffin oil at 10 percentage recorded highest colony diameter (6.50 cm) to control (8.70 cm).Regarding the sporulation, fungus sporulated well in corn oil at 10 percentage (1.83 x 108 spores / mL) followed by paraffin oil (1.80 x 108 spores /mL). Even though all the oils were compatible except pungam oil, paraffin oil may be encouraged, because of their rheology that may suit well for formulation.